Characteristics of Albizia Chinensis Wood Sawdust Briquette Product at High Compression Method - Adam Mandra Suwandi; Yolli Fernanda; Ambiyar Ambiyar; Andril Arafat (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
One of the biomass potentials that can be utilized is felled wood waste which can be used as an energy source. The advantage of biomass is that it can be renewed so that it triggers a sustainable energy source. Biomass energy that will be made into briquettes is processed and compressed so that the shape is more regular and has a high calorific value. In this study, wood waste will be used as a source of biomass. The test was carried out, namely the thermogravimetric test to determine the proximate content. The method used is using Sengon wood as a raw material with a particle size exceeding 18 mesh but not exceeding 30 mesh. Briquetting using a hydraulic pump and briquette hot molding, temperature variations of 250℃, 300℃, and 330℃ with a time of 10 minutes. The test was carried out, namely the thermogravimetric test to determine the proximate content of the briquettes. Applying pressure to the briquettes while simultaneously heating makes the briquettes strong. From 3 variations of temperature treatment, it was found that the temperature of 330℃ had a high carbon content and low volatility of all test samples. Salah satu potensi biomassa yang bisa dijadikan sebagai sumber energi adalah limbah kayu hasil tebangan. Kelebihan biomassa adalah dapat diperbaharui. Energi biomassa yang akan dibuat menjadi briket diolah dan dimampatkan sehingga bentuknya lebih teratur dan mempunyai nilai kalor yang tinggi. Penelitian ini akan menggunakan sampah kayu untuk sumber biomassa. Pengujian dilakukan yaitu uji thermogravimetric untuk mengetahui kandungan proximate. Metode yang digunakan adalah dengan bahan baku kayu sengon dengan ukuran partikel antara 18 mesh tetapi tidak lebih dari 30 mesh. Pembriketan dengan pompa hidrolik dan cetak panas briket, variasi temperature 250℃, 300℃ dan 330℃ dengan waktu selama 10 menit. Pengujian thermogravimetric dilakukan untuk mengetahui kandungan proximate dari briket. Pemberian tekanan pada briket sekaligus pemanasan menjadikan briket yang kuat, dari 3 variasi perlakuan suhu. didapatkan bahwa suhu 330℃ memiliki kandungan karbon yang tinggi dan volatile yang rendah dari semua sample uji.